1998
DOI: 10.1182/blood.v91.9.3509
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Platelet Recovery and Utilization in Patients After Myeloablative Therapy and Hematopoietic Stem Cell Transplantation

Abstract: An observational study was conducted at 18 transplant centers in the United States and Canada to characterize the platelet recovery of patients receiving myeloablative therapy and stem cell transplantation and to determine the clinical variables influencing recovery, determine platelet utilization and cost, and incidence of hemorrhagic events. The study included 789 evaluable patients transplanted in 1995. Clinical, laboratory, and outcome data were obtained from the medical records. Variables associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 22 publications
2
44
2
4
Order By: Relevance
“…PPGF was associated with shorter survival time, which is consistent with the previous studies [4,8,11,12]. Numerous studies have reported risk factors that influence platelet engraftment, such as myelotoxic agent, conditioning regimen intensity, stem cell source, and number of infused CD34 + cells or MNC [5,6,11,28]. Consistent with previous studies, our findings indicate that the CD34 + cell dose is crucial for better platelet engraftment [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…PPGF was associated with shorter survival time, which is consistent with the previous studies [4,8,11,12]. Numerous studies have reported risk factors that influence platelet engraftment, such as myelotoxic agent, conditioning regimen intensity, stem cell source, and number of infused CD34 + cells or MNC [5,6,11,28]. Consistent with previous studies, our findings indicate that the CD34 + cell dose is crucial for better platelet engraftment [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, no other studies have correlated PLT transfusion requirements with global markers of adverse clinical outcomes after HPCT such as NRM and all‐cause ICU admission. One study by Bernstein and colleagues, however, examined PLT use and time to PLT engraftment in patients undergoing HSCT and identified several baseline patient characteristics that are associated with increased transfusion needs and longer time to PLT recovery. Consistent with our findings, they reported that allogeneic transplant recipients received a higher number of PLT transfusions and had a longer time to PLT recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, they reported that allogeneic transplant recipients received a higher number of PLT transfusions and had a longer time to PLT recovery. Interestingly, most clinically significant bleeding events occurred when the morning PLT count was more than 20 ×10 9 /L and other transplant‐related variables such as mucositis, cystitis, and graft‐versus‐host disease were more significant predictors of bleeding risk than PLT count . Undoubtedly, patient factors such as underlying malignancy and extent of prior treatment and the intensity of the transplant conditioning regimen influence patient transfusion requirements and larger studies performed in a prospective fashion in more homogenous patient populations may provide greater insight.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also found that the platelet engraftment was poorer for patients with HCT‐CI scores of ≥3 ( P = 0.033). We speculate that this might be the result of direct damage of comorbidities on the marrow microenvironment , or that it might result from increases in a negative regulator of hematopoiesis, such as TNF‐α and IL‐6 . Therefore, a high comorbidity burden may well affect the platelet engraftment negatively.…”
Section: Discussionmentioning
confidence: 99%